Analysis of Systemic Violence and Social Inequality in The Purge (2013): A Marxist Theoretical Lens: Analisis Kekerasan Sistemik dan Kesenjangan Sosial dalam The Purge (2013): Lensa Teori Marxis - Abiyyu, Daffa Murfid; Nurhidayat (Journal of English Development, 2026)
This study analyzes systemic violence and social inequality represented in James DeMonaco's film The Purge (2013) using a Marxist theoretical lens. This study focuses on analyzing the three main pillars of Marxist theory: class domination, class struggle, and alienation, as represented in the visual elements, narrative, and characters in the film. This study uses a qualitative descriptive method with a focus on content analysis. This study interprets the film using Marxist concepts and compares the findings with contemporary academic studies on cinema and cases of social inequality. The results of this study show that The Purge depicts how capitalist ideology legitimizes violence, how resistance emerges symbolically, and how alienation destroys social and psychological structures. This study argues that The Purge functions not only as a dystopian horror film, but also as a symbol of ideological criticism of the capitalist system, which is relevant to both global and local conditions. These findings highlight the role of film as a cultural medium in social criticism and reinforce the relevance of Marxist theory in analyzing social inequality in modern society.